Toxicity Assessment of Lactococcus lactisIO-1 Used in Coconut Beverages against Artemia salina using Brine Shrimp Lethality Test - Ajibola, Olaide Olawunmi; Samuel, Lihan; Ahmad, Hussaini; Rosmawati, Saat; Idris, Adewale Ahmed; Wahab Abideen, Akinkunmi; Fazia, Mohamad Sinang; Ngieng, Ngui Sing; Adeyinka, Gbadebo Clement (2020)
Background and objective:Plant-based fermented foods containing favorable micro-organisms have been used to improve diets. Starter microorganisms may produce toxic compounds that are hazardous to consumers. Brine shrimp lethality test is a convenient and appropriate assay to check toxicity of samples. The aim of this study was to investigate toxicity of pasteurized coconut beverages at 70C, 80C and 90C for 25, 15 and 5 min, respectively, and unpasteurized coconut beverages fermented by Lactococcus lactisagainst Artemiasalina nauplii.